Bond strength of the interface between concrete substrate and overlay concrete containing fly ash exposed to high temperature. (March 2023) - Behforouz, Babak; Tavakoli, Davoud; Gharghani, Mehdigholi; Ashour, Ashraf
Abstract: Bond between substrate and overlay concretes is a key factor for the success of the repair method and significantly influences the structural performance of the repaired element. This study investigated the effect of fly ash and the surface preparation method on the bond strength of repaired concrete after exposure to high temperatures, that has not been comprehensively studied in the literature. For this purpose, overlay concretes containing 0, 5, 10, 15, and 20 % fly ash as a replacement by weight of cement were cast on the original concrete surface prepared by four methods namely, as-cast, wire brushed, grooved and grooved-wire brushed. The bond strength of the interface between concrete substrate and overlay concrete was evaluated after exposure to 23, 200, 400, and 600 °C temperatures for 1 h. The results showed that partial replacement of cement by fly ash in the overlay concrete increased the bond strength of repaired concrete by up to 71 %, depending on the amount of fly ash used, surface preparation method, and the temperature to which the sample was exposed. The maximum increase of bond strength was recorded for concrete containing 20 % fly ash when the wire brushed preparation method was adopted at temperature of 200 °C. However, surface preparation was the most influential parameter, achieving a bond strength gradual increase in order from as-cast, wire brushed, grooved to grooved-wire brushed methods. The results also showed that for most of the samples having similar surface preparation and the same percentage of fly ash, bond strength decreased with the increase of exposure to temperature; for example, for overlay concretes without fly ash, in as-cast and wire brushed surface preparation methods at temperatures of 400 and 600 °C, the bond strength has reached zero. On the other hand, for grooved and grooved-wire brushed surface preparation methods, the bond strength reduction was about 63 %, when temperature increased from 23 to 600 °C.